A European net wealth tax - Alexander Krenek; Margit Schratzenstaller (Austrian Institute of Economic Research (WIFO), 2018)
The increase of wealth inequality in many EU countries has spurred interest in wealth taxation. While taxes on wealth for a long time have played only a marginal role in the public finance and taxation literature, more recently a variety of arguments are brought forward in favour of (higher) wealth taxation. At the same time, tax competition has led to an almost complete disappearance of recurrent net wealth taxes in Europe. By dealing with non- and under-reporting in the Household and Consumption Survey (HFCS) data set provided by the European Central Bank, we are able to estimate the wealth distribution within 20 EU countries and the revenue potential of a progressive EU-wide net wealth tax.
Keywords: F55; H24; H87; 330; Net wealth tax; wealth taxation; wealth distribution; HFCS; top wealth holders